Siberian tiger quest [videorecording (DVD)] - Birkhead, Mike; Loncraine, Joe; Morgan, Chris, 1968-; Park, Sooyong (Filmmaker) (PBS Distribution, 2012)
Chris Morgan has tracked large predators in some of the wildest and most remote places on Earth. He now embarks on a challenge that would fulfill a lifelong dream -- to find and film a Siberian tiger living in the wild and free in Russia's far eastern forests. The film features the work of Korean cameraman Sooyong Park, the first individual ever to film Siberian tigers in the wild.